2006
DOI: 10.1021/ma052214c
|View full text |Cite
|
Sign up to set email alerts
|

Miscibility of Propylene−Ethylene Copolymer Blends

Abstract: Miscibility of homogeneous propylene/ethylene (P/E) copolymers of relatively narrow molecular weight distribution was studied as a function of constituent comonomer content. Polymers with up to 31 mol % ethylene were blended in pairs in order to vary the comonomer content difference. Binary blends were rapidly quenched from the melt to retain the phase morphology, and the phase volume fractions were obtained from AFM images. Copolymers of molecular weight about 200 kg mol-1 were miscible if the difference in e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 26 publications
1
29
1
Order By: Relevance
“…In binary blends of polypropylenes with small quantities of ethylene content, the presence of rubbery domains has been previously reported [26,32,58,59]. The situation is probably very similar in the case of PPR.…”
Section: Effect Of Ethylene Concentration On the Morphology And Dynammentioning
confidence: 57%
See 2 more Smart Citations
“…In binary blends of polypropylenes with small quantities of ethylene content, the presence of rubbery domains has been previously reported [26,32,58,59]. The situation is probably very similar in the case of PPR.…”
Section: Effect Of Ethylene Concentration On the Morphology And Dynammentioning
confidence: 57%
“…From this trend in mobility, it is most likely that chain segments with an amount of ethylene units above a certain concentration aggregate and form small (possibly nanoscopic) rubbery domains. Previously, it has been shown that phase separation can already occur in the molten state for metallocene-derived statistical ethylene e a-olefins copolymers [57,58]. The tendency for phase separation should be even larger for the samples studied here, as they were synthesized using ZN catalysis.…”
Section: Effect Of Ethylene Concentration On the Morphology And Dynammentioning
confidence: 74%
See 1 more Smart Citation
“…The interaction between neat PE and PP that we will use in the numerical calculations is x 1;0 ¼ x 0;1 ¼ 0:01 (see Introduction and ref. [25][26][27] ). For the coarse-grained chain this is replaced by the interactions between the beads as…”
Section: Histogram Constructionmentioning
confidence: 99%
“…[25][26][27][28] . In our analysis we will assume that all chains have same length of N ¼ 10 4 monomers with a Flory-Huggins parameter x ¼ 0.01 between the E and P monomers (xN ¼ 100); these are typical values that can easily be adjusted to specific samples.…”
Section: Introductionmentioning
confidence: 99%